Measurement of the inclusive isolated-photon production cross section in pp and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (The European physical journal. C, Particles and fields, 2025)
The ALICE Collaboration at the CERN LHC has measured the inclusive production cross section of isolated photons at midrapidity as a function of the photon transverse momentum pγT, in Pb-Pb collisions in different centrality intervals, and in pp collisions, at centre-of-momentum energy per nucleon pair of √sNN= 5.02 TeV. The photon transverse momentum range is between 10-14 and 40-140 GeV/c, depending on the collision system and on the Pb-Pb centrality class. The result extends to lower pγT than previously published results by the ATLAS and CMS experiments at the same collision energy. The covered pseudorapidity range is |η γ | < 0.67. The isolation selection is based on a charged particle isolation momentum threshold pT iso,ch = 1,5 GeV/c within a cone of radii R=0.2 and 0.4. The nuclear modification factor is calculated and found to be consistent with unity in all centrality classes, and also consistent with the HG-PYTHIA model, which describes the event selection and geometry biases that affect the centrality determination in peripheral Pb-Pb collisions. The measurement is compared to next-to-leading order perturbative QCD calculations and to the measurements of isolated photons and Z0 bosons from the CMS experiment, which are all found to be in agreement.
Im Titel steht der Ausdruck sNN unter dem Wurzelsymbol, NN ist dabei tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M.W. Menzel, A. Nath, K. Reyers, R. Schicker, F. Schlepper, J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone, B. Zhang und weitere 1042
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt
Gesehen am 20.01.2026